Optimisation of Mass Transport Parameters in a Polymer Electrolyte Membrane Electrolyser Using Factorial Design-of-Experiment - Majasan, Jude O.; Cho, Jason I. S.; Maier, Maximilian; Shearing, Paul R.; Brett, Dan J. L. (Frontiers in Energy Research, 2021)
Optimised mass transport is crucial for high current density operations in Polymer Electrolyte Membrane Water Electrolysers (PEMWEs). This study investigates the effect and interactions of mass transport parameters on the performance of a PEMWE using a 2^3 full-factorial Design-of-Experiments (DoE) approach with replication. The effects of anode flow-field design, anode porous transport layer and water flow rate on the cell performance were studied. At 95% confidence level, the result shows that all three factors and their two-way interactions significantly affect the cell performance. Among them, the water flow rate showed the most significant contribution, followed by the interaction between the flow-field and the porous transport layer (PTL). A regression model was developed to relate the cell performance and the mass transfer parameters. Results of analysis of variance (ANOVA), regression analysis and R2 test indicated good accuracy of the model. The combination of a parallel flow-field, a small average pore diameter of PTL and high anode water flow rate were found to give the best PEMWE cell performance. The DoE is shown to be a suitable method for investigating interactions and optimising the operating conditions to maximise PEMWE performance.